Developing Initial Assessments for Learning Needs of Children Aged 5-6 - Rahmah Novianti; Firda Tuti Yani; Fatma Rizki Intan (UNIK (Jurnal Ilmiah Pendidikan Luar Biasa), 2026)
Initial assessment in Early Childhood Education plays a crucial role in identifying children’s developmental levels, learning readiness, and potential developmental delays before formal learning begins. This study aims to develop a valid and practical initial assessment instrument that can be used by teachers to identify children’s cognitive, language, and social-emotional development, as well as to support early screening of potential special needs. This research employed a Research and Development (R&D) approach using the ADDIE model. The study was conducted in two kindergartens in Palembang. Involving two expert validators and ten teachers, with 48 children aged 5-6 years observed as assessment subjects. The result showed that the instrument achieved a validity level of 83.82% (valid category) and a practical level of 86.75% (very practical category). The findings indicate that the developed instrument is easy to use, understandable, and useful for teachers in identifying children’s initial conditions. Furthermore, the instrument has potential as an early screening tool to identify children who may require further assessment for developmental delays or special education needs.